The Effect of Healing Touch-Dhikr Therapy on Quality Sleep of Patients With Diabetes Mellitus on The Work Area Kaliwungu Health Center - Anggi Dita Puspita; Sukarmin Sukarmin; Diana Tri Lestari (CV. Inara, 2026)
Poor sleep quality is a common problem in patients with diabetes mellitus which can negatively impact metabolic control and reduce the patient's quality of life. Therefore, this study is important to find alternative non-pharmacological therapies to improve the sleep quality of diabetic patients. The main purpose of this study is to determine the effect of healing touch-dhikr therapy on the sleep quality of patients with diabetes mellitus in the Kaliwungu Health Center Working Area. This study uses a quantitative method, namely quasi experimental with a pretest-posttest with control group design. The sample consisted of 78 respondents who were selected through purposive sampling and divided into two groups: the intervention group (n = 39) and the control group (n = 39). The healing touch-dhikr intervention was given for seven days with a duration of 15–30 minutes per session. The data collection instrument used the Pittsburgh Sleep Quality Index (PSQI). Data analysis was carried out by dependent t-test and independent t-test test. The results showed a significant decrease in PSQI scores in both groups (p<0.001). The average sleep quality score of the intervention group decreased from 11.92 to 6.00 (difference of 5.92), while in the control group it decreased from 12.10 to 10.05 (difference of 2.05). Although both showed significant changes, the larger decline in the intervention group showed that healing touch–dhikr therapy was more clinically and statistically effective in improving the sleep quality of patients with diabetes mellitus. This is supported by an independent t-test showing a significant difference between the two groups (p< 0.001), which indicates the effectiveness of the intervention. Thus, it can be concluded that healing touch-dhikr therapy has a significant and clinically effective effect in improving the quality of sleep in patients with diabetes mellitus. This research supports the application of spiritual-based non-pharmacological interventions in nursing practice as a holistic approach that pays attention to the physical, psychological, and spiritual aspects of patients.